2006
DOI: 10.1001/archsurg.141.10.1006
|View full text |Cite
|
Sign up to set email alerts
|

Selection Criteria for Simultaneous Resection in Patients With Synchronous Liver Metastasis

Abstract: Hypothesis: While simultaneous resection has been shown to be safe and effective in patients with synchronous metastasis, neoadjuvant chemotherapy followed by hepatectomy has gradually gained acceptance for both initially nonresectable metastasis and resectable metastasis. The boundary between these treatments is becoming unclear. We hypothesized that factors associated with colorectal cancer may play an important role in the prognosis of patients with synchronous metastasis and may be useful for identifying p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
76
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 40 publications
(61 reference statements)
7
76
0
3
Order By: Relevance
“…The factor that most influenced the OS was related to the surgery, with R1/R2 resections increasing 6-fold the risk of death. Similar results were reported in most studies (10,(37)(38)(39), although recent papers suggested that the results of R1 resection are mitigated in present by the effective oncologic therapies (40)(41)(42)(43)(44)(45). However, prospective R2 resections are still an absolute contraindication to liver resection for CLMs and whenever possible, a negative resection margin larger than 1 mm should be achieved (36,(46)(47)(48).…”
Section: Discussion Discussionsupporting
confidence: 78%
“…The factor that most influenced the OS was related to the surgery, with R1/R2 resections increasing 6-fold the risk of death. Similar results were reported in most studies (10,(37)(38)(39), although recent papers suggested that the results of R1 resection are mitigated in present by the effective oncologic therapies (40)(41)(42)(43)(44)(45). However, prospective R2 resections are still an absolute contraindication to liver resection for CLMs and whenever possible, a negative resection margin larger than 1 mm should be achieved (36,(46)(47)(48).…”
Section: Discussion Discussionsupporting
confidence: 78%
“…Performance status has been shown to be associated with clinical outcomes, and while we controlled for comorbidities and age, poor performance status may have been associated with both access to care and poor outcome. We also do not have information on the individual serum carcinoembryonic antigen levels or the specific nature of the metastases in each patient, for example, the number of metastases, sizes of metastases, and other sites of metastases (Minagawa et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…At presentation, 23-51% of patients diagnosed with colorectal cancer have synchronous liver metastases (10). Patients with synchronous disease require co-ordination of multiple providers in order to optimize the timing and sequence of therapies, with the management of rectal cancer and synchronous metastatic disease posing an especially difficult dilemma.…”
Section: Introductionmentioning
confidence: 99%